STRENGTHENING HALAL TOURISM GOVERNANCE IN PEKALONGAN: A Maqasid-Based Collaborative Governance Framework within Siyasah Dusturiyah - Mustofa Mustofa; Hisam Ahyani; Irsyansyah Irsyansyah; Attabik Hasan Ma'ruf; Muhamad Buchori; Ihwanul Muadib; Agus Supriadi; Salisu Muhammad Gumel (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2026)
The rapid growth of halal tourism has generated increasing global attention toward governance models that integrate religious values with sustainable and accountable public policy frameworks. As Muslim-friendly tourism expands across diverse jurisdictions, regulatory implementation often faces structural, institutional, and coordination challenges. In Indonesia, the Central Java Governor Regulation No. 40 of 2023 on Muslim-Friendly Tourism seeks to regulate halal services, worship facilities, and information transparency to accommodate Muslim travelers. This study evaluates the implementation of this regulation in Pekalongan City using a juridical-empirical approach. Data were collected through 12 in-depth interviews with key stakeholders, including tourism actors, religious leaders, and government officials, complemented by field observations. The findings reveal that although the regulation formally reflects Islamic legal values, particularly maq??id al-shar?‘ah, its implementation remains suboptimal due to weak inter-agency coordination, limited public literacy, and the absence of measurable evaluation indicators. This study proposes a Maq??id-based collaborative governance model that integrates Islamic legal objectives, consumer protection principles, and cross-sectoral coordination mechanisms. The model contributes to the broader discourse on halal tourism governance by offering an analytically grounded framework for strengthening accountability, stakeholder collaboration, and policy sustainability in Muslim-friendly tourism regulation.